(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The study addresses the research question of how ICT infrastructure can promote competitive advantage based on cloud accounting in Jordanian banks and moderated by the efficiency of cybersecurity. The issue discussed is the lack of knowledge about the ways in which secure ICT systems can be strategically used to transform financial operations within a digitally developing banking sector. Based on the paradigm of Design Scientific Research, the research design adopted a qualitative conceptual design, secondary data and expert opinion were used to produce a theoretical framework based on the Resource-Based View and the Market-Based View. The findings indicate that an efficient ICT infrastructure supports timely decision-making, flexibility in operations, and cost-efficiency, and that cybersecurity supplements such performance significantly. The study recommends investing additional capital into safe cyber infrastructure and regulatory disclosure. Among the implications are the ability to position cybersecurity as a strategic enabler and the ability to view cloud accounting as a fundamental source of sustained competitive advantage in emerging economies.